Relationship between Financial Inclusion and Monetary Policy on Economic Growth: Evidence from Panel Data Draw from a Sample of Developing Countries - Salisu, Ali (European Scientific Journal, ESJ, 2022)
Financial inclusion augments the ability to acquire economic resources and ensure the livelihood of individuals in different economic systems. Rising the accessibility of financial infrastructure stimulates the economic power of human beings. The study analyses the relationship between financial inclusion, and monetary policy on the economic growth of Developing Countries using panel data from 2010 to 2020. The panel unit root tests indicated that real gross domestic product, exchange rate, and interest rate are stationary at the level. In contrast, Automated Teller Machines, Bank branches, inflation rate, and money supply are stationary at the first difference. The Generalized Method of Moment (GMM) results shows that bank branches have a positive but statistically significant effect on real gross domestic product in the selected developing countries. The automated Teller Machine has a positive but statistically insignificant effect on real gross domestic product in the selected developing countries. The interest rate has a negative but statistically significant effect on real gross domestic product in the selected developing countries. The inflation rate negatively but statistically significant effect on real gross domestic product in the selected developing countries. Money supply has a negative but statistically significant effect on real gross domestic product in the selected developing countries. The exchange rate negatively and statistically insignificant effect on real gross domestic product in the selected developing countries. The study concluded that both financial inclusion and monetary policy have a positive and significant effect on economic growth in developing countries for the period under study. The study recommends that Government should ensure that commercial banks perform a perfect banking system and ensure that customer satisfaction is met in terms of providing varieties of ATMs, opening new branches, etc by so doing economic growth could be achieved in developing countries. In taking austerity measures on the economy the central authority should not employ only monetary policy but rather a combination of fiscal policy in order to stabilize the economy and achieve higher economic growth in developing economies.